Control of non-linear actuator of artificial muscles for the use in low-cost robotics prosthetics limbs - Atikah N.A.; Weng L.Y.; Anuar A.; Fat C.C.; Sahari K.S.M.; Abidin I.Z. (Institute of Physics Publishing, 2023)
Actuators; Artificial limbs; Costs; Engineering research; Linear control systems; Manufacture; Muscle; Position control; Prosthetics; Robotics; Artificial muscle; Electrically conductive; Fluid materials; Force generation; Manufacturing cost; Non linear control; Performance characteristics; Prosthetic limbs; Linear actuators